Впровадження змін та інновацій в органах державної влади у контексті євроінтеграції України - Макарчук, Юліана Вікторівна (Київський національний університет імені Тараса Шевченка, 2026)
В першому розділі розкрито концептуальні основи впровадження інновацій у систему державного управління. Автором уточнено понятійно-категоріальний апарат, зокрема класифікацію інновацій у сфері державного управління. Досліджено еволюцію принципів належного врядування та їх трансформацію під впливом стандартів SIGMA. В другому розділі досліджено стан реалізації реформ та ідентифіковано ключові перешкоди на шляху ефективної імплементації реформ. Окрему увагу приділено успішним кейсам цифрової трансформації, зокрема екосистемі «Дія», яка розглядається як інструмент радикального подолання бюрократичних бар’єрів та корупційних ризиків. На основі порівняльного аналізу з європейським досвідом доведено пряму кореляцію між спрощенням реєстраційних процедур та рівнем активності громадянського суспільства. У третьому розділі розроблено практичні рекомендації та модель управління змінами, адаптовану до умов воєнного та повоєнного відновлення. Обґрунтовано стратегічну роль громадського сектору як суб’єкта верифікації реформ через цифрові інструменти. Визначено, що синергія цифрових технологій та партисипативної демократії є головною запорукою вдосконалення системи державного управління.

Makarchuk Y. V. Implementation of changes and innovations in state authority bodies in the context of Ukraine's European integration. – Qualifying scientific work as a manuscript. Qualifying scientific work for obtaining an educational degree at the second level of higher education (Master's degree), field of study: D "Business, Administration and Law", specialty D4 "Public Management and Administration". – Educational and Scientific Institute of Public Administration and Civil Service of Taras Shevchenko National University of Kyiv, Kyiv, Ukraine, 2026. The first section reveals the conceptual foundations of introducing innovations into the public administration system. The author specifies the conceptual and categorical apparatus, in particular, the classification of innovations in the field of public administration. The evolution of the principles of good governance and their transformation under the influence of SIGMA standards is studied. The second section analyzes the state of reform implementation and identifies key obstacles to the effective implementation of reforms. Special attention is paid to successful cases of digital transformation, in particular the “Diia” ecosystem, which is considered a tool for radically overcoming bureaucratic barriers and corruption risks. Based on a comparative analysis with the European experience, a direct correlation between the simplification of registration procedures and the level of civil society activity is proven. The third section develops practical recommendations and a change management model adapted to the conditions of war and post-war recovery. The strategic role of the public sector as a subject of verification of reforms through digital tools is substantiated. It has been determined that the synergy of digital technologies and participatory democracy is the main key to improving the public administration system.
Implementation of changes and innovations in state authority bodies in the context of Ukraine's European integration
Keywords: управління змінами; інновації; європейський досвід; цифровізація; інститути громадянського суспільства; євроінтеграція; державне управління; change management; innovation; European experience; digitalization; civil society institutions; European integration; public administration